Crisis and reconfiguration: economic and political changes in the Brazilian accumulation regime in the XXI century - Marcelo Soares Bandeira de Mello Filho; Diogo Oliveira Santos (Revue de la Régulation)
The main objective of this work is to demonstrate that Brazil has experienced, since the end of 2016, a reconfiguration of the financial and extractive accumulation regime and a change in the ruling power bloc. Based on the Regulation Theory, an analysis of the Brazilian economy is carried out to understand the current transformations. The recent liberal reforms are assessed to demonstrate how they imply an accumulation regime reconfiguration, affecting institutional forms and consolidating the power bloc hegemonized by the agrarian and financial bourgeoisie. Among other effects, these reforms deepen State subordination to the monetary and financial regime, expand the control of the bourgeoisie over the wage relation and reinforce the commodity-exporting sector. It is concluded that the ongoing reconfiguration increases the country’s dependence on international economic and financial cycles because it takes necessary instruments of economic intervention away from the State. Moreover, it reduces internal control over the competition with foreign companies in the national territory, reinforces the commodity-exporting sector and makes mass consumption more pro-cyclical. This reconfiguration implies a partial reversal in the internalization of the dynamic centre of Brazilian capitalism that occurred during the import substitution industrialization process.